Biologické úcinky resveratrolu a dalsích obsahových látek vína - Kollár, P; Hotolová, H (Ceska a Slovenska farmacie, 2003)
In recent years many scientific papers have been published concerning the positive effects of wine and its active principles, the polyphenol resveratrol being the most widely discussed compound. The results of epidemiological and experimental studies in man, animals, and in vitro have shown that polyphenols contained in wine, tea, fruit, and vegetables exert a positive effect on both the progression and regression of atherosclerosis, possess an anticancerogenic action, and due to their antioxidative effects they act against other processes connected with the reactive forms of oxygen production and lipid peroxydation in the blood plasma and membranes. Experimental findings have shown that resveratrol protects the cardiovascular system, affects lipid metabolism, and inhibits low-density lipoproteins (LDL) oxidation and blood platelet aggregation. In addition, this natural product is able to inhibit the growth of some tumours and possesses antiinflammatory properties and a number of other biological effects. This report aims to describe and characterize in a summary the biological properties of the principal active principles of wine--flavonoids and polyphenols, with a detailed focus on resveratrol, which has been described as the most interesting agent.
Keywords: Animals; resveratrol; Wine; stilbeny; lidé; Antioxidants; zvířata; Stilbenes; víno; antioxidancia; Resveratrol; Humans